Facile solvothermal synthesis of MnFe2O4 hollow nanospheres and their photocatalytic degradation of benzene investigated by in situ FTIR - Shen, Y.; Wang, L.; Wu, Y.; Li, Xin Yong; Zhao, Q.; Hou, Y.; Teng, W. (Elsevier, 2015)
MnFe2O4 hollow nanospheres were successfully fabricated via a facile one-pot solvothermal method. The prepared products were characterized by XRD, SEM, TEM, FTIR and UV–Vis absorption spectroscopy analyses. Benzene can be effectively degradated on the MnFe2O4 nanospheres when irradiated with visible light. By using the in situ FTIR technique, ethyl acetate, carboxylic acid, aldehyde and acetylene could be regarded as the intermediate products, and CO2 was produced as the final mineralization product during the reaction process. Hydroxyl radicals were confirmed as active species in the photocatalytic reaction by the photoluminescence technique.